PENCEGAHAN KONSUMERISME SEJAK DINI MELALUI PENDIDIKAN EKONOMI DASAR - Ni Putu Wiwin Setyari; Made Kembar Sri Budhi; I Komang Gde Bendesa; I Ketut Sudibia; I Gusti Bagus Indrajaya; Sudarsana Arka; Ni Putu Martini Dewi; I Gusti Wayan Murjana Yasa (Jurnal Abdi Insani, 2022)
Current excessive activities have endangered the nation, so it is necessary to raise public awareness about the importance of financial management. In order to prevent the character of consumerism in elementary school students, as well as in an effort to provide financial intelligence, economic education needs to be given from an early age. The process of character education itself needs to be carried out from an early age and must be maximized at elementary school age. Therefore it is appropriate to provide economic education for elementary school students. This community service activity aims to provide an understanding of basic economic education and its implementation in everyday life for early childhood, in this case elementary school students. This activity is carried out through the planning stage, namely the preparation of materials and learning methods. Furthermore, at the stage of providing material, it is carried out through lectures, discussions, demonstrations, and quizzes, followed by FGD. Implementation of activities that were well followed by students of SD Negeri 12 Kesiman, as the target of the activity. Students receive material on the introduction of money, the “5 Don't” Movement, introduction and recording of savings, and basic entrepreneurship. The students have also done demonstrations related to recording and making simple piggy banks as tips. Furthermore, the results of the FGD with the teachers concluded that in the future economic education activities would be directed to the development of a circular economy in schools, such as through waste banks. Another effort is to provide training for students to recycle inorganic waste to be efficient and economically feasible. The students have been able to understand material about early childhood economic education, such as an introduction to money, savings, and basic entrepreneurship.